2021
DOI: 10.1016/j.ejca.2021.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of hysterectomy and bilateral salpingo-oophorectomy in carriers of pathogenic mismatch repair variants: a Prospective Lynch Syndrome Database report

Abstract: and Marianne Haeusler for their efforts over many years. The CCFR graciously thanks the generous contributions of their study participants and dedication of study staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…The timing and options of RRS can be individualized based on childbearing potential, comorbidities, menopause status, family history and types of germline PVs. 43,109 As mentioned above, the risks of LS-EC varied based on the types of germline PVs, and the median age at onset in path_MSH6 carriers was higher than that in path_MLH1 and path_MSH2 carriers. 17,22 Path_MSH6 carriers are recommended to undergo RRS after 40 years of age, while either path_MLH1 or path_MSH2 carriers might consider risk-reducing surgery at approximately 35 years of age when they no longer need to be fertile.…”
Section: Preventive Surgerymentioning
confidence: 92%
See 2 more Smart Citations
“…The timing and options of RRS can be individualized based on childbearing potential, comorbidities, menopause status, family history and types of germline PVs. 43,109 As mentioned above, the risks of LS-EC varied based on the types of germline PVs, and the median age at onset in path_MSH6 carriers was higher than that in path_MLH1 and path_MSH2 carriers. 17,22 Path_MSH6 carriers are recommended to undergo RRS after 40 years of age, while either path_MLH1 or path_MSH2 carriers might consider risk-reducing surgery at approximately 35 years of age when they no longer need to be fertile.…”
Section: Preventive Surgerymentioning
confidence: 92%
“…Considering the lower risk of EC in path_PMS2 carriers, the role of RRS for path_PMS2 carriers needs further evaluation. Seppälä et al 109 indicated that hysterectomy and/or BSO were performed in 32%, 30%, 18% and 13% of path_MLH1 , path_MSH2 , path_MSH6 and path_PMS2 carriers aged 40‐49 years, respectively, which showed that the uptake of RRS was low and did not correspond well with the current guidelines and age or gene‐associated predicted risks. In addition, a newly published study indicated that little clinical benefit was gained by performing RRS before 40 years old, and there was no significant survival benefit to performing BSO in premenopausal path_MSH6 and path_PMS2 carriers, 110 indicating that guidelines need to be updated consistently based on new data to facilitate optimal individual clinical decision.…”
Section: Preventionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Lynch syndrome, risk reducing hysterectomy and salpingo-oophorectomy is cost effective at age 4046 and prevents 13–45% of endometrial cancers if performed at age 40 years, and 4–18% if performed at age 60 3. Despite this, uptake by 50 years of age is low, at 9–28% for hysterectomy and 13–26% for salpingo-oophorectomy,47 and centers across the world vary in their approach to recommending risk reducing surgery 48. Female Lynch syndrome carriers regard cancer surveillance to be very important, and would opt for more regular investigations if offered 49.…”
Section: Discussionmentioning
confidence: 99%
“… 43 However, Seppala et al observed that uptake of risk-reducing gynecological surgery in LS aligned poorly regarding gene- and age-associated risk and did not correspond well with current clinical guidelines. 44 …”
Section: Hereditary Gynecologic Cancer Syndromesmentioning
confidence: 99%